Relationships of stressors and opportunism in cross-border exchange partnership contexts: When and how monitoring matters - Zaefarian, Ghasem; Robson, Matthew J.; Najafi-Tavani, Zhaleh; Spyropoulou, Stavroula (Journal of International Business Studies, 2023)
Abstract Transaction costs economics work has argued that monitoring procedures are needed to evaluate the extent to which overseas partners comply with their obligations. We posit that the transactional theory of stress can also inform on how to distinguish opportunists from non-opportunists. Synthesizing these two theories and using a three-study, multimethod design, we examine whether different types of stressors influence opportunism, and how and under what conditions such links are moderated by monitoring. Based on separate surveys of 209 Chinese subsidiaries’ and 232 Chinese suppliers’ cross-border intrafirm and interfirm partnerships with headquarters and buyers, respectively – in conjunction with an add-on experimental study conducted in the US – the results suggest challenge and hindrance stressors impact opportunism differently. The former exhibits a U-shaped, and the latter a positive, relationship with opportunism. We thus observe the importance of both the level and type of stress. Further, the international exchange context matters for monitoring’s efficacy. Monitoring steepens the U-shaped challenge stressors–opportunism relationship in intrafirm (not interfirm) partnerships. It however weakens the positive hindrance stressors–opportunism relationship in interfirm (not intrafirm) partnerships. The findings inform managers on when and how to use monitoring to control challenge and hindrance stressors’ links to opportunism in these contexts.